Dust-to-gas ratio and metallicity gradients in DustPedia galaxies. Issue Volume 14:Issue A30(2018) (August 2018) - Bianchi, Simone; ,
Abstract: Far-infrared photometric observations from the Herschel Space Observatory offer the opportunity to study the dust-to-gas ratio at a resolved scale in nearby galaxies. The amount, and gradient, of solid-phase metals can thus be compared with metallicity measurements in the gas phase. We describe our preliminary work on the topic with data from the DustPedia project.